2010
DOI: 10.1007/s12040-009-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of quasi-3D DC resistivity imaging data using artificial neural networks

Abstract: The objective of this paper is to investigate the applicability of artificial neural networks in inverting quasi-3D DC resistivity imaging data. An electrical resistivity imaging survey was carried out along seven parallel lines using a dipole-dipole array to confirm the validation of the results of an inversion using an artificial neural network technique. The model used to produce synthetic data to train the artificial neural network was a homogeneous medium of 100 Ωm resistivity with an embedded anomalous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Method Traditional machine learning converts real-world problems into mathematical models, trains historical data models, and finally converts the new data to real-world solutions. Among them, the artificial neural network is suitable for solving this kind of structure is complex changes of the underground geological inversion problem, not to need for data analysis and modeling, able to recognize and deal with the background and the law is not clear information [27][28][29], however, it is very hard to complex geological region has certain limitation, for example, hard training large networks and depth, In the inversion process, there are problems such as over-fitting, slow convergence rate and low accuracy [7,[30][31][32]. Based on this, domestic and foreign geophysicists have carried out in-depth research on this issue and put forward a series of improved methods, such as: Jiang et al proposed COSFLA optimization based on wavelet packet denoising and ANFIS network [33] and resistivity imaging inversion based on kernel principal component wavelet neural network based on ISFLA training [34], which achieved good results by using kernel principal component wavelet neural network.…”
Section: Based On Traditional Machine Learning Inversionmentioning
confidence: 99%
“…Method Traditional machine learning converts real-world problems into mathematical models, trains historical data models, and finally converts the new data to real-world solutions. Among them, the artificial neural network is suitable for solving this kind of structure is complex changes of the underground geological inversion problem, not to need for data analysis and modeling, able to recognize and deal with the background and the law is not clear information [27][28][29], however, it is very hard to complex geological region has certain limitation, for example, hard training large networks and depth, In the inversion process, there are problems such as over-fitting, slow convergence rate and low accuracy [7,[30][31][32]. Based on this, domestic and foreign geophysicists have carried out in-depth research on this issue and put forward a series of improved methods, such as: Jiang et al proposed COSFLA optimization based on wavelet packet denoising and ANFIS network [33] and resistivity imaging inversion based on kernel principal component wavelet neural network based on ISFLA training [34], which achieved good results by using kernel principal component wavelet neural network.…”
Section: Based On Traditional Machine Learning Inversionmentioning
confidence: 99%
“…It is used to prevent the system from converging to a local minimum. The momentum and learning rate terms were analyzed by Ahmad Neyamadpour et al (2010) and suggested the learning rate of 0.01, and a momentum coefficient of 0.2.…”
Section: Feed-forward Back Propagation With Levenberg-marquardt (Ffbpmentioning
confidence: 99%
“…The momentum term (α) dampens the amount of weight change by adding in a portion of the weight change from the previous iteration. The momentum term is credited with smoothing out large changes in the weights and with helping the network converge faster when the error is changing in the correct direction (Neyamadpour et al 2010). In this study, the estimation is started with a learning rate of 0.3 according to the guidelines suggested by Neuner (2010).…”
Section: Ann Design and Optimisationmentioning
confidence: 99%